2014
DOI: 10.4236/pp.2014.54048
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Drug-Drug Interaction in Prescription Dispensed by Community and Hospital Pharmacy

Abstract: Objective: To analyze the use of all subsidized prescription drugs including their use of drug combination generally accepted as carrying a risk of severe interactions. Methodology: In a cross sectional study, we analyzed all prescriptions (n = 1014) involving two or more drugs dispensed to the population (age range 4-85 years) from all pharmacies, clinics and hospitals. Data were stratified by age and sex, and frequency of common interacting drugs. Potential drug interactions were classified according to clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 21 publications
4
27
1
5
Order By: Relevance
“…Patients with hypertension, diabetes, and other chronic diseases are more likely to experience polypharmacy. [1,9,10] Polypharmacy may cause ADRs owing to the drug additive effect, synergism, duplication, DIs, discontinuation of treatment, and physiological antagonism. It was reported that patients aged above 65 years use an average of two to six prescribed drugs and 1 to 3.4 nonprescribed drugs.…”
Section: Polypharmacymentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with hypertension, diabetes, and other chronic diseases are more likely to experience polypharmacy. [1,9,10] Polypharmacy may cause ADRs owing to the drug additive effect, synergism, duplication, DIs, discontinuation of treatment, and physiological antagonism. It was reported that patients aged above 65 years use an average of two to six prescribed drugs and 1 to 3.4 nonprescribed drugs.…”
Section: Polypharmacymentioning
confidence: 99%
“…The incidence of DIs is 40% in patients taking five drugs and perhaps up to 80% in patients taking seven drugs. [1,7,10] The female gender was established to be more prone to DIs owing to their frequent hospital visits. [1,7,10] In a developed country such as Switzerland, the incidence of DIs was 23%.…”
Section: Incidence Of Drug Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This population also having a higher prevalence of chronic disease because of lower immunity as well as thy use typical drug therapy for several health related issues. 9,10 Possibility of manifestation of interaction was very difficult to identify due to 11  A large number of an herbal product was easily available in the market.  Herbs consist of multiple constituents of various pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%